PEMAKNAAN MAHASISWA SURABAYA TERHADAP ISU KEMATIAN AFFAN KURNIAWAN DI MEDIA SOSIAL INSTAGRAM : STUDI FENOMENOLOGI - Prayoga, Agastya Reza; Ahmad Zamzamy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines how Surabaya university students construct meaning around the death of Affan Kurniawan, an online motorcycle-taxi (ojol) driver who died during the August 2025 protest, as the issue circulated on Instagram. Using Alfred Schutz's social phenomenology, the research explores three interpretive indicators: stock of knowledge, typification, and motives (because-motives and in-order-to motives). A qualitative phenomenological design was employed, involving eight purposively selected undergraduate informants from various universities in Surabaya who were active Instagram users and had been exposed to the issue. Data were collected through in-depth interviews, documentation of Instagram content, and non-participant observation, then analyzed using the Miles and Huberman interactive model together with data, investigator, and theory triangulation. Findings show that informants' interpretations were shaped by prior accumulated knowledge from family background, education, organizational experience, and habitual media consumption. Typification allowed informants to classify the actors involved — police, protesters, civilians, and social media users — into familiar categories that guided how responsibility and meaning were assigned, with some informants revising their initial categorization of the police as new information emerged. Motives combining past experience and present goals, such as seeking justice or expressing empathy, further shaped how students responded, ranging from silent reflection to active participation in solidarity actions. The study concludes that meaning-making around Affan Kurniawan's death was not a spontaneous individual process but a socially constructed one, built through the interplay of prior knowledge, categorical thinking, and continuous exposure to Instagram's discursive space.